Herding in the Nordic Stock Markets; Evidence from Finland, Sweden and Denmark - Rouvinen, Joakim (My University, 2018)
This study assesses herding behaviour and how it occurs on the separate Nordic stock markets of Finland, Sweden and Denmark during the time period of 2007-2018. Herding can be characterised as investors abandoning their own initial vision and then following a common market consensus. This behaviour can be categorised as either rational or irrational. The study utilises the CSAD methodology established by Chiang and Zheng (2010) to detect market-wide herding during the chosen sample period of 2007-2018. The method comprises calculating the non-linear relationship between dispersions of individual asset or stock returns compared to the full market portfolio return. When observing the entire sample period, none of the selected markets, Finland, Sweden, Denmark, display herding behaviour. When exposed to subsample testing, where the entire sample period is divided into one-year periods, results demonstrate that Sweden experienced herding behaviour in 2013. Additionally, the study finds evidence that herding is most likely to occur there on down-market days. Finland nor Denmark display significant herding on either the entire sample period or during subsample periods. Moreover, Finland or Denmark did not display significant herding occurring on either up- or down -market days. This study also recognises the importance of the US and European markets on smaller markets. It is found that Denmark in particular is prone to herding around the German and US markets. Furthermore, stock return dispersions from the US and Germany affect all of the three selected markets. Empirical results suggest that Sweden displays the most significant evidence of herding for the entire sample period according to all of the different regression estimates which were tested. These results are partially inconsistent with previous studies. The greatest contribution this study makes is the observation of why results are inconsistent particularly in Finland. It is suggested that the difference in time periods renders different results. This in extension would suggest that at least the Finnish stock market has developed over the course of time and does not suffer as extensively from market anomalies.
Keywords: Herding; stock market; behavioural finance; Nordic markets; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|